2009
DOI: 10.1016/j.jesp.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Faces of politicians: Babyfacedness predicts inferred competence but not electoral success

Abstract: Recent research has documented that competent-looking political candidates do better in U.S. elections and that babyfaced individuals are generally perceived to be less competent than maturefaced individuals. Taken together, this suggests that babyfaced political candidates are perceived as less competent and therefore fare worse in elections. We test this hypothesis, making use of photograph-based judgments by 2,772 respondents of the facial appearance of 1,785 Finnish political candidates. Our results confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 21 publications
2
75
0
2
Order By: Relevance
“…ii Following the 'truth of consensus' method (Banducci et al, 2008;Benjamin and Shapiro, 2009;Poutvaara et al, 2009), we calculated the average of the independent evaluations across raters for every picture.…”
Section: Experimental Design(s)mentioning
confidence: 99%
“…ii Following the 'truth of consensus' method (Banducci et al, 2008;Benjamin and Shapiro, 2009;Poutvaara et al, 2009), we calculated the average of the independent evaluations across raters for every picture.…”
Section: Experimental Design(s)mentioning
confidence: 99%
“…Yet, the human mind often relies on superficial cues to form judgments or make decisions, and the choice of which leader to select is no exception: A large and growing literature shows that facial appearances predict success in reaching prestigious leadership positions (Antonakis & Jacquart, 2013;Olivola & Todorov, 2010a). In the domain of politics, numerous studies have found that more competent-looking political candidates garner larger vote shares (e.g., Antonakis & Dalgas, 2009, Ballew & Todorov, 2007Poutvaara et al, 2009; for a review of this literature, see Olivola & Todorov, 2010a). Voters also seem to favor more attractive candidates (Berggren, Jordahl, & Poutvaara, 2010;Efran & Patterson, 1974) and those who look stereotypically like members of their preferred political party (Olivola, Sussman, Tsetsos, Kang, & Todorov, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The facial appearance of political candidates and their electoral success are related: better-looking candidates win more votes (Todorov et al, 2005;Ballew and Todorov, 2007;Antonakis and Dalgas, 2009;Benjamin and Shapiro, 2009;Poutvaara et al, 2009;King and Leigh, 2009;Berggren et al, 2010;Rule at al., 2010;Lawson et al, 2010;Olivola and Todorov, 2010). While this has been established as a general relationship, none of the studies look at differences in beauty or in beauty premia between political candidates from the left and from the right.…”
Section: Introductionmentioning
confidence: 99%